Peptide maps comparing subunits of maize chloroplast and type II nuclear DNA-dependent RNA polymerases. - Kidd, G H (1979)
Both one- and two-dimensional peptide mapping techniques have been used to compare the 180-kilodalton subunits from maize chloroplast and type II nuclear DNA-dependent RNA polymerases (nucleosidetriphosphate:RNA nucleotidyltransferase, EC 2.7.7.6). Despite their similar molecular mass, these 180-kilodalton subunits are not the same. Also, two-dimensional tryptic maps of the 160-, 43-, and 28-kilodalton polypeptides from maize type II nuclear RNA polymerase and of the 140-, 42-, and 27-kilodalton polypeptides from maize chloroplast RNA polymerase show that each of these six polypeptides is unique.